2005
DOI: 10.1111/j.1523-1755.2005.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia induces endothelial dysfunction

Abstract: Hyperuricemic rats have a decrease in serum nitric oxide which is reversed by lowering uric acid levels. Soluble uric acid also impairs nitric oxide generation in cultured endothelial cells. Thus, hyperuricemia induces endothelial dysfunction; this may provide insight into a pathogenic mechanism by which uric acid may induce hypertension and vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
749
6
29

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,061 publications
(833 citation statements)
references
References 10 publications
28
749
6
29
Order By: Relevance
“…[16][17][18] UA potently decreases endothelial nitric oxide bioavailability and induces endothelial dysfunction. 33 Elevated SUA levels were also associated with the increased generation of free radicals 34 and oxidative stress, which could abolish endothelium-dependent vasodilatation, leading to hypertension. 35 However, other studies have suggested that UA was an effective antioxidant, 36,37 and the exact role of UA in oxidation (pro-oxidant or antioxidant) remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] UA potently decreases endothelial nitric oxide bioavailability and induces endothelial dysfunction. 33 Elevated SUA levels were also associated with the increased generation of free radicals 34 and oxidative stress, which could abolish endothelium-dependent vasodilatation, leading to hypertension. 35 However, other studies have suggested that UA was an effective antioxidant, 36,37 and the exact role of UA in oxidation (pro-oxidant or antioxidant) remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The consequent increase in plasma uric acid was indeed associated with a decrease in plasma nitrites/nitrates (NOx). Similarly, direct exposure of endothelial cells to uric acid slightly reduces basal or VEGF-stimulated NO production (40). Thus, uric acid can dose-dependently reduce NO bioavailability.…”
Section: Uric Acid: Antioxidant or Pro-oxidant?mentioning
confidence: 96%
“…5,13,14,50 It has been suggested that hyperuricemia inhibits nitric oxide availability and decreases insulin-mediated glucose uptake in skeletal muscle and may, therefore, have a role in the development of the metabolic syndrome. 51,52 Other studies have suggested that hyperinsulinemia, a consequence of the metabolic syndrome, enhances the tubular reabsorption of uric acid and that this occurs concurrently with a decrease in sodium and potassium excretion, leading to elevated BP. 53 In both instances, the association between abdominal obesity and high BP is mediated by hyperinsulinemia, 16 which is consistent with the notion of a common exposure to hyperinsulinemia (and obesity) in the relation between SUA and BP.…”
Section: Discussionmentioning
confidence: 99%